An interpretation of the idiom קוץ ציך in Psalm 35:19 - Kotze, Z. (Journal for Semitics, 2010)
The expression קוץ ציך in Ps 35:19 that is usually translated ''to wink the eye'' has been identified as an insidiously malicious gesture that communicates hostility. To date, however, the conceptual content of this expression has not been adequately detailed against the background of the ancient Israelite belief regarding the magical powers of the eye. This paper seeks to investigate the scope of the metonym קוץ ציך ''to pinch the eye'' in order to come to a verifiable interpretation of the locution. It is argued that the focus of this figurative expression is the causation of harm to another person and that the idiom was motivated by the ancient Israelite belief in the evil eye.
paid